Community Structures of Bacteria, Archaea, and Eukaryotic Microbes in the Freshwater Glacier Lake Yukidori-Ike in Langhovde, East Antarctica - Aoi Chaya; Norio Kurosawa; Akinori Kawamata; Makiko Kosugi; Satoshi Imura (Diversity, 2019)
Since most studies about community structures of microorganisms in Antarctic terrestrial lakes using molecular biological tools are mainly focused on bacteria, limited information is available about archaeal and eukaryotic microbial diversity. In this study, the biodiversity of microorganisms belonging to all three domains in a typical Antarctic freshwater glacier lake (Yukidori-Ike) was revealed using small subunit ribosomal RNA (SSU rRNA) clone library analysis. The bacterial clones were grouped into 102 operational taxonomic units (OTUs) and showed significant biodiversity. Betaproteobacteria were most frequently detected, followed by Cyanobacteria, Bacteroidetes, and Firmicutes as major lineages. In contrast to the bacterial diversity, much lower archaeal diversity, consisting of only two OTUs of methanogens, was observed. In the eukaryotic microbial community consisting of 20 OTUs, Tardigradal DNA was remarkably frequently detected. Genera affiliated with the phyla Ciliophora, Cryptomycota, Chlorophyta, Bacillariophyta, and Apusozoa were also detected. The biodiversity and species compositions of the whole microbial community of Lake Yukidori-Ike are similar to those of freshwater environments in temperate regions but are different from saline lakes in Antarctica, indicating that the salinity seems to affect the microbial composition more than the temperature.